2008
DOI: 10.1073/pnas.0802631105
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of structural form

Abstract: Algorithms for finding structure in data have become increasingly important both as tools for scientific data analysis and as models of human learning, yet they suffer from a critical limitation. Scientists discover qualitatively new forms of structure in observed data: For instance, Linnaeus recognized the hierarchical organization of biological species, and Mendeleev recognized the periodic structure of the chemical elements. Analogous insights play a pivotal role in cognitive development: Children discover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
441
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(467 citation statements)
references
References 39 publications
(30 reference statements)
6
441
0
4
Order By: Relevance
“…Without clear constraints, it is hard to derive testable predictions. However, we can evaluate the specific model of linear orderings that Kemp and Tenenbaum (2008) provided. This model has two basic problems as a psychological proposal.…”
Section: Relation To Previous Models Of Learning Dimensional Represenmentioning
confidence: 99%
“…Without clear constraints, it is hard to derive testable predictions. However, we can evaluate the specific model of linear orderings that Kemp and Tenenbaum (2008) provided. This model has two basic problems as a psychological proposal.…”
Section: Relation To Previous Models Of Learning Dimensional Represenmentioning
confidence: 99%
“…Recent advances in computational modeling have provided formal accounts of how abstract knowledge can both be learned and support learning from sparse data across content domains [60][61][62][63][64][65]. Some of children's inferential abilities can be captured with these models (see, e.g., [61,66], for reviews and analysis).…”
Section: Opinionmentioning
confidence: 99%
“…However, the likelihood favors h1 and h3, because colds and lung cancer are more likely than the flu to generate coughing. Thus the posterior probability favors the hypothesis that the child has a cold (example from, and detailed account available in [62]). Bayes' law also provides a formal account unifying what might otherwise seem like very different routes to uncertainty and exploration.…”
Section: Box 1 Hierarchical Bayesian Inference Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was successful in simulating infants' behavior, which suggested that a common mechanism may operate during category learning throughout the life span. This type of modeling that uses the same mechanism to model child and adult behavior has been an active area of research in other modeling approaches as well (e.g., probabilistic modeling: Kemp & Tenenbaum, 2008; dynamic field theory: Perone et al, 2011).…”
Section: Resultsmentioning
confidence: 99%